Latitudinal distributions of the species richness, phylogenetic diversity, and functional diversity of fleas and their small mammalian hosts in four geographic quadrants - Krasnov, Boris R. (2023)
We studied latitudinal patterns in the species richness (SR), the phylogenetic diversity (PD), and the functional diversity (FD) of fleas and their mammalian hosts. We asked whether these patterns in either fleas, hosts, or both 1) conform to a classical latitudinal gradient; 2) vary geographically; and 3) differ between fleas and hosts. We also asked whether the patterns of PD and FD follow those of SR. We collected data on the latitudinal distribution of 1022 flea and 900 mammal species from literature sources and calculated the SR, PD, and FD of both groups in 1° latitude bands. Then, we used broken-stick regression models to analyse separately the latitudinal variation of 1) each diversity facet and 2) fleas and hosts in each geographic quadrant. The classical latitudinal gradient pattern was not found in either fleas or hosts across any facet of diversity or geographic quadrant, except for the PD of fleas in the southeastern quadrant and the FD of hosts in the southwestern quadrant. Latitudinal patterns of the SR, PD and FD of fleas and hosts differed substantially between geographic quadrants. Furthermore, the latitudinal distributions of flea and host SR were similar in three of four quadrants (except the northeastern quadrant), whereas the latitudinal distributions of flea and host PD were similar in the southwestern quadrant only. No similarity in flea versus host FD was revealed. The latitudinal patterns of flea and host PD and FD mostly did not follow those of their SR. We conclude that latitudinal gradients of species richness and phylogenetic and functional diversity appeared not to be universal phenomena. Instead, the latitudinal distributions of these diversity facets represent an interplay of ecological (current and past) and historical processes. For parasites, the processes acting on hosts add another layer of complexity underlying their latitudinal diversity patterns.